Phase II, open‐label trial of lapatinib and vinorelbine in women with previously treated HER2‐positive metastatic breast cancer. Issue 4 (28th October 2014) - Chan, Arlene; Shannon, Catherine; de Boer, Richard; Baron‐Hay, Sally; Redfern, Andrew; Bauwens, Astrid; Craft, Paul; Webb, Suzanne; Townsend, Amanda; Kotasek, Dusan
Abstract Aim To evaluate the efficacy and tolerability of lapatinib (L) and intravenous vinorelbine (V) in patients with metastatic HER2‐positive breast cancer who have previously received two lines of anti‐HER2 therapy (i.e. trastuzumab [T] with chemotherapy and lapatinib with capecitabine [LC]). Method Consenting patients with measurable or evaluable disease and normal cardiac function who had progressed were recruited. Patients received LV (lapatinib 1250 mg orally daily, vinorelbine 20 mg/m2 intravenously on days 1 and 8 every 3 weeks) until progressive disease, intolerable toxicity or patient request. Results The trial was closed early following inclusion of 19 patients due to slow accrual. Ten, five and four patients had received two, three and more than four lines of chemotherapy with T and LC, respectively, prior to study entry. Patients received a median of 5 cycles (range 1–18) of LV. Confirmed partial response was seen in 2 of 16 patients with measurable disease (12.5%); stable disease >24 weeks was seen in two patients (10.5%) with a clinical benefit rate of 20%. Fatigue and any grade neutropenia occurred commonly, but grade 4 severity occurred in only 5 and 11%, respectively. There were no episodes of cardiac dysfunction and no treatment‐related deaths. The median progression‐free survival was 3.9 months and overall survival (OS) was 9.1 months. Conclusion The combination of LV demonstrated modest efficacy but was well tolerated. This combination may be of benefit to those patients who are unable to access the newer anti‐HER2 agents and the low rate of treatment‐emergent adverse effects will enable patients' symptoms, such as pain, to be minimized.